2021
DOI: 10.3390/nu13051552
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic and Oxytocin Combination Therapy in Patients with Autism Spectrum Disorder: A Randomized, Double-Blinded, Placebo-Controlled Pilot Trial

Abstract: Autism spectrum disorder (ASD) is a rapidly growing neurodevelopmental disorder. Both probiotics and oxytocin were reported to have therapeutic potential; however, the combination therapy has not yet been studied. We conducted a randomized, double-blinded, placebo-controlled, 2-stage pilot trial in 35 individuals with ASD aged 3–20 years (median = 10.30 years). Subjects were randomly assigned to receive daily Lactobacillus plantarum PS128 probiotic (6 × 1010 CFUs) or a placebo for 28 weeks; starting on week 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 74 publications
(88 reference statements)
0
62
0
2
Order By: Relevance
“…Recent studies have shown that the gut microbiota is involved in the bidirectional regulation of the intestinal and central nervous systems through neural, endocrine, metabolic, and immune pathways ( Osadchiy et al, 2019 ). It is believed that microecological therapies that improve the gut microbiota can alleviate some gastrointestinal symptoms and ASD symptoms in ASD patients, so far, some reports have already proved that gut microbiota intervention therapy is helpful for ASD improvement ( Wang et al, 2020 ; Kong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the gut microbiota is involved in the bidirectional regulation of the intestinal and central nervous systems through neural, endocrine, metabolic, and immune pathways ( Osadchiy et al, 2019 ). It is believed that microecological therapies that improve the gut microbiota can alleviate some gastrointestinal symptoms and ASD symptoms in ASD patients, so far, some reports have already proved that gut microbiota intervention therapy is helpful for ASD improvement ( Wang et al, 2020 ; Kong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic product has been reported to ameliorate anxiety, hyperactivity, impulse, and opposition/defiance behaviors [ 47 ], and has more positive effects in children than adolescents with ASD [ 48 ]. Combined with oxytocin treatment, PS128 increases ASD patients’ favorable gut microbiome network hubs [ 49 ]. Furthermore, it may have a potential benefit for mood disorders, as the main finding of this study suggested that PS128 may be able to reduce depressive symptoms in insomniacs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this study, Mensi et al, 2021 found that autistic children and adolescents who received L. plantarum PS128 had greater improvements in terms of global functioning characterized by increased attention, communication skills, and personal autonomies. In another randomized, double-blind, placebo-controlled pilot trial, individuals with ASD aged 3–20 years who received oral probiotic L. plantarum PS128 and intranasal oxytocin elicited significant improvements in ASD core socio-behavioral symptoms, clinical global functioning, and gut microbiome dysbiosis ( Kong et al, 2021c ). It was revealed that the two treatments are supposed to have synergistic interactions in the regulation of the gut–brain axis.…”
Section: Novel Therapeutic Approaches Targeting Gut Microbiome For Asdmentioning
confidence: 99%